Consumers Buying Behavior Towards Piracy Products in Kathmandu Valley - Gautam, Manish (Nepalese Journal of Business, 2025)
This study examines consumers’ buying behavior towards piracy products in Kathmandu Valley. Consumers’ perception on piracy is the dependent variable. Similarly, the selected independent variables are peer pressure, price, easily accessible, design and packaging, ethical awareness and socioeconomic status. The study is based on primary data of consumers’ residing in Kathmandu Valley with 140 respondents. To achieve the purpose of the study, the structured questionnaire is prepared. The Kendall’s tau correlation coefficients and regression models are estimated to test the relationship, significance and impact of determinants of factors affecting consumers’ perception on piracy products. The study showed that peer pressure has a positive impact on consumers’ perception on piracy. It implies that increase in pressure from the peers towards pirated products stimulate the buying behavior of consumers towards piracy products. Likewise, price has a positive impact on consumers’ perception on piracy. It implies that fair price of pirated products stimulate the buying behavior of consumers towards piracy products. Similarly, easily accessible has a positive impact on consumers’ perception on piracy. It indicates that increase in easily accessible pirated product stimulate the buying behavior of consumers towards piracy products. Similarly, design and packaging have a positive impact on consumers’ perception on piracy, indicating that well designed and packaged pirated product stimulate the buying behavior of consumers towards piracy products. Likewise, ethical awareness has a positive impact on consumers’ perception on piracy. It indicates that increase in ethical awareness of pirated products stimulate the buying behavior of consumers towards piracy products. Likewise, socioeconomic status has a positive impact on consumers ‘perception on piracy. It implies that better consumers’ socioeconomic status stimulate the buying behavior of consumers towards piracy products.